Phase I Clinical Trial of Vinorelbine in Tumor‐Bearing Cats. (10th May 2013) - Pierro, J.A; Mallett, C.L.; Saba, C.F.
Abstract : Background: Vinorelbine (VRL) has been investigated in dogs, but its use in cats has not been studied. Hypothesis/Objectives: To determine the maximal tolerated dose (MTD) and dose‐limiting toxicity (DLT) of VRL in tumor‐bearing cats. Animals: Cats were included in this prospective phase I trial if they had confirmed malignancy, received ≥1 VRL treatment, and had adequate follow‐up. Previous treatment was acceptable, but concurrent chemotherapy or radiotherapy was not permitted. Methods: Using a modified phase I design, cats were enrolled in cohorts of 3 at a starting dosage of 9 mg/m 2 . Cats tolerating the first treatment well were eligible to receive additional VRL treatments at escalating dosages; escalations beyond the perceived MTD were permitted based on individual tolerance. Intended treatment interval was 7 days. Patient histories, physical examinations, and complete blood counts were performed weekly. Results: Nineteen cats were included. Sixty‐one VRL treatments were administered. Median number of treatments was 2 (range, 1–9). Starting dosages were 9–12 mg/m 2 . Maximal dosage administered was 15.5 mg/m 2 . The MTD was 11.5 mg/m 2 . Acute DLTs were neutropenia, vomiting, and nephrotoxicity. Other notable toxicities were weight loss and anemia. Conclusions and Clinical Importance: Vinorelbine is tolerated in cats at a weekly interval. Recommended starting dosage is 11.5 mg/m 2 . Neutropenia was transient, lasting <7 days; vomiting was self‐limiting in most cases. Although VRL‐associated nephrotoxicity has not been reported, potential attribution of this toxicity to VRL must not be discounted. Further investigation of the efficacy of VRL in feline malignancies is warranted.